AUTHOR'S RIGHT IS NOT ONLY COPYRIGHT - Sardjono, Agus (UI Scholars Hub, 2021)
This article discusses the difference between the concept of Author's Right and Copyright. These two concepts are often mistakenly considered to be inter-changeable. The purpose of this article is to help readers obtain a better insight into the basic concept of Author's Right and Copyright.